Profile of Cesarean Sections Since the BPJS Era: Profil Seksio Sesarea pada Era BPJS - Mohd. Andalas; Cut R. Maharani; Raudhatul Jannah; Siti Harisah; Muhammad Haekal; Ichsan (Indonesian Socety of Obstetrics and Gynecology, 2020)
Objective: to find out the profile of caesarean section in dr. Zainoel Abidin Hospital since the BPJS era. Methods: This study was a descriptive-observational with retrospective design. The data were obtained in March-April 2017. We collected 3656 data from medical record period January 1st, 2014- December 31st, 2016. Results: The finding showed there were 1669 vaginal deliveries (45,65%) and 1987 caesarean sections (54,35%). The most frequent causes to caesarean sections were induction failure (49,77%), cephalopelvic disproportion (14,33%), pregnancy induced hypertension (11,21%), malpresentation (8,91), and antepartum haemorrhage (4,33%). Conclusion: The incidence of caesarean sections in dr. Zainoel Abidin Hospital since the BPJS era was 54,35%, increased by 13,29% than the year of 2011-2013 (41,06%) with the most frequent cause is induction failure (49,77%). Keywords: Antepartum haemorrhage, BPJS, Caesarean section, Induction failure, Pregnancy induced hypertension, Tertiary referral hospital. Abstrak Tujuan: Mengetahui profil persalinan seksio sesarea di RSUD dr. Zainoel Abidin Banda Aceh pada era BPJS. Metode: Penelitian deskriptif-observasional dengan desain studi retrospektif. Pengambilan data dimulai dari bulan Maret-April 2017. Sebanyak 3656 data dikumpulkan dari rekam medik periode 1 Januari 2014- 31 Desember 2016. Hasil: Terdapat 1669 kasus persalinan pervaginam (45,65%) dan 1987 kasus seksio sesarea (54,35%). Indikasi terbanyak yang menyertai seksio sesarea adalah gagal induksi (49,77%), cephalopelvic disproportion (14,33%), hipertensi dalam kehamilan (11,21%), malpresentasi (8,91%), dan perdarahan antepartum (4,33%). Kesimpulan: Angka seksio sesarea di RSUD dr. Zainoel Abidin meningkat 13,29% sejak berlakunya BPJS (1 Januari 2014-31 Desember 2016) mencapai 54,35% dibandingkan tahun 2011-2013 (41,07%) dengan indikasi terbanyak gagal induksi (49,77%). Kata kunci: Perdarahan Antepartum, BPJS, Seksio sesarea, Gagal Induksi, Hipertensi dalam kehamilan, RS Rujukan Tersier.